Genomic tools and cDNA derived markers for butterflies - ALEXIE PAPANICOLAOU; MATHIEU JORON; W. OWEN MCMILLAN; MARK L. BLAXTER; CHRIS D. JIGGINS (Molecular Ecology, 2005)
The Lepidoptera have long been used as examples in the study of evolution, but some questions remain difficult to resolve due to a lack of molecular genetic data. However, as technology improves, genomic tools are becoming increasingly available to tackle unanswered evolutionary questions. Here we have used expressed sequence tags (ESTs) to develop genetic markers for two Müllerian mimic species, Heliconius melpomene and Heliconius erato . In total 1363 ESTs were generated, representing 330 gene objects in H. melpomene and 431 in H. erato . User‐friendly bioinformatic tools were used to construct a nonredundant database of these putative genes (available at http://www.heliconius.org ), and annotate them with blast similarity searches, InterPro matches and Gene Ontology terms. This database will be continually updated with EST sequences for the Papilionideae as they become publicly available, providing a tool for gene finding in the butterflies. Alignments of the Heliconius sequences with putative homologues derived from Bombyx mori or other public data sets were used to identify conserved PCR priming sites, and develop 55 markers that can be amplified from genomic DNA in both H. erato and H. melpomene . These markers will be used for comparative linkage mapping in Heliconius and will have applications in other phylogenetic and genomic studies in the Lepidoptera.